Evaluation Of Physical Education Learning During Covid-19 At Jombang District Junior High School - Anggoro Saputro, Arnaz (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
The purpose of this study was to evaluate the implementation of online physical learning at the Jombang District Public Middle School during the Covid-19 pandemic using the CIPP model (contect, input, process, and product). This research is a qualitative descriptive research using quantitative and qualitative approaches (mixed method). The population in the study were teachers of Physical Education at State Junior High Schools in Jombang Regency. The sampling technique used proportional random sampling as much as 25% of the total Physical Education teachers in Jombang Regency Junior High Schools. The research instruments used questionnaires, interviews, and documentation. Quantitative data were analyzed using percentage techniques, while qualitative data were performed through data presentation, reduction and drawing conclusions. The results of research on the implementation of Physical Education learning during the Covid-19 pandemic showed that (1) the results of the context evaluation related to the vision, mission, targets and goals on an ongoing basis obtained very good results, the average value of context = 4.49 from the maximum value 5.00, (2) input: equipment and facilities, new student recruitment system, funding, media, theoretical and practical teaching material modules, the assessment instruments used are very good, the average value of input = 4.39, (3) process: theoretical and practical teaching systems and methods, as well as the e-modules used are of very good quality, because the average value of process = 4.38, and (4) product: the value of theory, practice, and the level of physical fitness of students is very high good because the average value of product = 4.20. Thus it can be concluded that the evaluation of the implementation of online Physical Education learning at the Jombang District Public Middle School during the Covid-19 pandemic was very good.